Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian terhadap Perilaku Manajemen Keuangan pada Pelaku UMKM Binaan PT. Pertamina Hulu Rokan dan Kabupaten Bengkalis - Rosmida; Husni Mubarak (ABEC Indonesia, 2022)
This study entitled The Effect of Financial Knowledge, Financial Attitudes and Personality on Financial Management Behavior on UMKM Actors fostered by PT. Pertamina Hulu Rokan and Bengkalis Regency. The purpose of the study was to determine the effect of financial knowledge, financial attitudes and personality on financial management behavior. The total population is 15,409 UMKM entrepreneurs in Bengkalis Regency. By using the Slovin formula and a margin of error of 5%, a sample of 390 respondents was obtained. By using SPSS 22, the results obtained that financial knowledge has a positive effect on financial management behavior, financial attitudes have a positive effect on financial management behavior, and personality also has a positive effect on financial management behavior. These results can be used as the basis for the Bengkalis State Polytechnic to continue to work together with the Regional Government to provide motivation and teach how to manage finances well for UMKM entrepreneurs so that the regional economy continues to improve in the future.